ЭКСТРАКЦИЯ ЦЕРИЯ (III) И ИТТРИЯ (III) КАРБОНОВЫМИ КИСЛОТАМИ ИЗ НИТРАТНЫХ СРЕД - Чиркст Д.Э.; Литвинова Т.Е.; Старшинова В.С.; Рощин Г.С.; Луцкий Д.С. (My University, 2006)
Получены данные по экстракции церия (III) и иттрия (III) растворами олеиновой и нафтеновой кислот в о-ксилоле из нитратных сред. По зависимостям коэффициента рапределения от рН и состава органической и водной фаз вычислены константы и энергии Гиббса экстракционного равновесия, определен состав сольватных комплексов.

Experimental data on solvent extraction of cerium (III) and yttrium (III) by solutions of oleinic and naphthenic acids in o-dimethylbenzene was obtained. After mathematical analysis of the dependences of the distribution coefficient from pH and composition of organic and aqueous phases was determined the structure and composition of solvate complexes and value of the Gibbs free energies and reaction equilibrium constant.
Keywords: 541.124.127:66.081